Firing costs: eurosclerosis or eurosuccesses? - Yu-Fu Chen; Dennis J. Snower; Zoega Gylfi (Department of Economic Studies, University of Dundee, 1999)
In this paper we analyse the employment implications of firing restrictions. We find that when a recession is expected and the trend rate of productivity growth is small, a rise in firing costs affects mainly the hiring decision. Thus there is a negative effect on average employment. When, on the other hand, a boom is expected and the rate of productivity growth is large, firing costs affect mainly the firing decision. Then, as a result, average employment is increased. Our analysis suggests that while firing restrictions might have stimulated employment and reduced unemployment in Europe in the first two decades following World War II - when large supply shocks were absent and the average rate of growth was high - these same restrictions may have had the opposite effects in the 1970s and 1980s, when significant negative supply shocks occurred.
Keywords: E32; J23; J24; J54; 330; firing restrictions; stochastic demand; hiring and firing; real options; Kündigungsschutz; Arbeitsnachfrage; Kosten; Konjunktur; Theorie